Stock Investing For Dummies - Mladjenovic, Paul (Tantor Media, Inc., 2019)
Updated with new and revised material to reflect the current market, this new edition of Stock Investing For Dummies gives you proven strategies for selecting and managing profitable investments, no matter what the conditions. You'll find out how to navigate the new economic landscape and choose the right stock for different situations-with real-world examples that show you how to maximize your portfolio. The economic and global events affecting stock investors have been dramatic and present new challenges and opportunities for investors and money managers at every level. With the help of this guide, you'll quickly and easily navigate an ever-changing stock market with plain-English tips and information on ETFs, new rules, exchanges, and investment vehicles, as well as the latest information on the European debt crisis. - Incorporate stocks into your investment portfolio - Manage risk and ride out the market's ups and downs - Explore new investment opportunities Stock Investing For Dummies is an essential book for anyone looking for trusted, comprehensive guidance to ensure their investments grow.